In-vitro antibacterial activity of Rhus javanica against multidrug-resistant uro-pathogens - Saud, Bhavan; Paudel, T.; Sharma, T.; Gyawali, M.; Dhungana, G.; Shrestha, V.; Shrestha, R.K.; Bhusal, N. (Janaki Medical College Journal of Medical Science, 2019)
Background and Objectives: Antibiotic resistance is emerging as a major public health concern. From the ancient time in history, different plants and herbs have been known to have medicinal value. Rhus javanica has been found to show antibacterial activity against pathogenic bacteria. Thus, present study is designed to investigate the prevalence of urinary tract infection causing bacterial pathogens, its antibiogram and effect of Rhus javanica in standard in-vitro condition against multidrug-resistant. Material and Methods: Cross-sectional study was conducted in urinary tract infection suspected patients visiting a clinic in Kalimati, Kathmandu, from July to December 2017. A total of 133 midstream urine samples were collected and cultured in MacConkey agar and Blood agar media and isolates were identified by standard biochemical tests. Antibiotic susceptibility testing was performed according to Clinical and Laboratory Standard Institute (CLSI) guideline. Leaves extract of Rhus javanica was obtained by maceration using 50.0% methanol and susceptibility testing was performed by using cork borer method in Mueller-Hinton agar. Results: Out of total 133 samples, 35.3%showed significant bacterial growth (i.e. 105 cfu/ml) on agar plate. The most predominant organism was Escherichia coli 17.3%, followed by Enterococcus faecalis 6.8%, Klebsiella pneumoniae 3.8%, Pseudomonas aeruginosa 3.0%, Proteus vulgaris 2.3%, and Staphylococcus aureus 2.3%. Out of 47 isolates, 53.2% were Multi Drug Resistant (MDR). Various concentrations of the crude extract used (25, 50, 75 and 100 mg/ml) showed susceptibility to all the bacterial pathogens isolated, with the diameter of zone of inhibition ranging from 12 to 28 mm. Conclusion: Methanolic extract of Rhus javanica showed antibacterial activity against multidrug-resistant isolates of bacterial uropathogens in standard in-vitro condition.